Further contributions to the Coleoptera fauna of New Brunswick with an addition to the fauna of Nova Scotia, Canada - Webster, Reginald P. (Zookeys, 2016)
Abstract. This paper treats 134 new records of Coleoptera for the province of New Brunswick, Canada from the following 41 families: Gyrinidae, Carabidae, Dytiscidae, Histeridae, Leiodidae, Scarabaeidae, Scirtidae, Buprestidae, Elmidae, Limnichidae, Heteroceridae, Ptilodactylidae, Eucnemidae, Throscidae, Elateridae, Lampyridae, Cantharidae, Dermestidae, Bostrichidae, Ptinidae, Cleridae, Melyridae, Monotomidae, Cryptophagidae, Silvanidae, Laemophloeidae, Nitidulidae, Endomychidae, Coccinellidae, Corylophidae, Latridiidae, Tetratomidae, Melandryidae, Mordellidae, Tenebrionidae, Mycteridae, Pyrochroidae, Aderidae, Scraptiidae, Megalopodidae, and Chrysomelidae. Among these, the following four species are newly recorded from Canada: Dirrhagofarsus ernae Otto, Muona & McClarin (Eucnemidae), Athous equestris (LeConte) (Elateridae), Ernobius opicus Fall (Ptinidae), and Stelidota coenosa Erichson (Nitidulidae). The Family Limnichidae is newly reported for New Brunswick, and one species is added to the fauna of Nova Scotia. Stephostethus productus Rosenhauer (Latridiidae), Tetratoma (Abstrulia) variegata Casey (Tetratomidae), and Chauliognathus marginatus (Fabricius) (Cantharidae) are removed from the faunal list of New Brunswick, and additional records of Lacconotus punctatus LeConte (Mycteridae) are presented and discussed. Lindgren funnel traps provided specimens for 104 (78%) of the species and were the sole source of specimens for 89 (66%) of the species reported here, suggesting they are a very useful tool for sampling Coleoptera fauna in the forests of New Brunswick.